The Effect of Social Media Use on Interest Learning Vocational Students in DKI Jakarta - Wadah, Virahma; Busyra, Nur (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Discussing students' interest in social media has pros and cons. Negative perspectives are seen, such as the degradation of learning activities when students access social media daily. Still, other discussions emphasize the importance of social media as a good gap or opportunity for more interactive learning. Interesting to study, this study aims to determine the effect of social media on interest in education. One hundred four respondents (Vocational Students in DKI Jakarta) were recruited to complete the research questionnaire. The research procedure consists of testing the instrument's validity-reliability, classical assumptions (normality and linearity), and simple linear regression analysis (t-test and the coefficient of determination). The study's results accept the alternative hypothesis that " social media influences students' learning interest". The social media regression coefficient increases learning interest by 1,026 units, and the determinant coefficient is 77.2%. This paper convinces academics that "there is a gap or opportunity for how social media can be a good momentum to accelerate student interest in learning in the future". The essence of the research findings emphasizes scientific discussion about the possibilities of social media as the latest fiber or instrument to be executed by teachers and students in an educational atmosphere.